2019
DOI: 10.1016/j.jelectrocard.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

SPICED-ACS: Study of the potential impact of a computer-generated ECG diagnostic algorithmic certainty index in STEMI diagnosis: Towards transparent AI

Abstract: BackgroundComputerised electrocardiogram (ECG) interpretation diagnostic algorithms have been developed to guide clinical decisions like with ST segment elevation myocardial infarction (STEMI) where time in decision making is critical. These computer-generated diagnoses have been proven to strongly influence the final ECG diagnosis by the clinician; often called automation bias. However, the computerised diagnosis may be inaccurate and could result in a wrong or delayed treatment harm to the patient. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In ACS, an increase in these cardiac enzymes provides further diagnostic relevance [62]. Previous studies have suggested that ECGs proved invaluable in the CCU setting [63], as was the case in the CCU of KAUH.…”
Section: Procedures Performedmentioning
confidence: 98%
“…In ACS, an increase in these cardiac enzymes provides further diagnostic relevance [62]. Previous studies have suggested that ECGs proved invaluable in the CCU setting [63], as was the case in the CCU of KAUH.…”
Section: Procedures Performedmentioning
confidence: 98%
“…In this systematic review and meta-analysis, of the 1138 articles initially identified, 78 studies (enrolling a total of 10 056 participants) reported accuracy data (Figure 1). For 2 studies, data were reported in several different publications; in each case, we abstracted 1 report (the most complete). The eTable in the Supplement summarizes the key features of study designs and tests.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one studies involved medical students (n = 4256 participants), 42 studies involved postgraduate physicians (n = 2379), 11 studies involved noncardiologist practicing physicians (n = 1074), and 10 studies involved cardiologists or cardiology fellows (n = 2094); 4 mixed-participant studies did not report training level–specific sample sizes (n = 253). Twenty-six studies were randomized trials, 11 studies were 2-group nonrandomized comparisons, 19 studies were single-group pre-post comparisons, and 22 studies were cross-sectional (single time point). Twenty-two studies were identified as surveys .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, most of the systems use wireless and wearable devices for data acquisition and were designed for diagnosis purposes [166][167][168]. Other ECG monitoring systems mainly focus on the interpretation of diagnostic algorithms [88,166,169,170]. Arrhythmia diagnosis is one of the most common diseases diagnosed based on ECG signals [171][172][173][174].…”
Section: Service-based Monitoring Systemsmentioning
confidence: 99%